Development and characterization of plasticized starch‐based biocomposites with soy pulp as reinforcement filler. Issue 6 (7th June 2012) - Behera, Ajaya Kumar; Avancha, Sridevi; Sen, Ramkrishna; Adhikari, Basudam
Abstract Soy pulp, a byproduct of soymilk industry, was used in varying amount as reinforcement filler with thermoplastic starch, to develop and characterize starch–soy (SS) composites. The composite filled with 10 wt % soy pulp showed 112% and 98% increment in tensile and flexural strength, respectively. Fourier transform infrared spectrum of composite revealed occurrence of chemical bonding between hydroxyl group of soy pulp and that of starch matrix. The optimized composite containing 10 wt % soy pulp, with maximum mechanical strength was found thermally stable up to 312°C. Water absorption of these composites was enhanced with the increase in filler loading due to increase in hydrophilicity as evident from lowering of contact angle value. These composites are expected to be ecofriendly as soy pulp and starch are biodegradable in nature. The SS pulp composites so developed and characterized find potential application as disposable and packaging items. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013